2006
DOI: 10.1080/02640410400022185
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of pre-cooling and water ingestion on thermoregulation and physical capacity during exercise in a hot environment

Abstract: The aim of the present study was to determine the combined effects of pre-cooling and water ingestion on thermoregulatory responses and exercise capacity at 32 degrees C and 80% relative humidity. Nine untrained males exercised for 60 min on a cycle ergometer at 60% maximal oxygen uptake (VO2max) (first exercise bout) under four separate conditions: No Water intake, Pre-cooling, Water ingestion, and a combination of pre-cooling and water ingestion (Combined). To evaluate the efficacy of these conditions on exe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
69
1
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(75 citation statements)
references
References 27 publications
4
69
1
1
Order By: Relevance
“…[11][12][13][14][15][16][17][18][19][20][21] Direct comparisons with the magnitude of ergogenic effect observed in previous studies are limited because authors of only 2 studies 3,4 used the same protocol as we did, and only Kay et al 4 used the same mode of exercise. Kay et al 4 observed a 6.0% (900 m) improvement in performance when using an identical exercise protocol after 60 minutes of coolwater immersion, and Booth et al 3 observed a 4.2% improvement in distance run in 30 minutes after 60 minutes of coolwater immersion.…”
Section: Precooling Effectmentioning
confidence: 78%
“…[11][12][13][14][15][16][17][18][19][20][21] Direct comparisons with the magnitude of ergogenic effect observed in previous studies are limited because authors of only 2 studies 3,4 used the same protocol as we did, and only Kay et al 4 used the same mode of exercise. Kay et al 4 observed a 6.0% (900 m) improvement in performance when using an identical exercise protocol after 60 minutes of coolwater immersion, and Booth et al 3 observed a 4.2% improvement in distance run in 30 minutes after 60 minutes of coolwater immersion.…”
Section: Precooling Effectmentioning
confidence: 78%
“…Induced cold state by low temperature exposure may be considered as an important stressing agent [2]. Consolidated data from the literature point towards the existence of myocardial structural lesions resulting from the exposure of animals to extreme low temperature [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…In another study, the combination of cold water immersion and cold fluid ingestion that resulted in the lowest initial T c resulted in the longest time to 2max in the heat (32 °C ) (Hasegawa et al, 2006).…”
Section: Precoolingmentioning
confidence: 99%